Common Hazards to Consider during the Manufacturing of Poultry Feed - Jessica Brown; Ashley Cavallo; Lindsay Zombek; Carli Brown; Arianna Minnie; Melinda Dennis; Gabrielle Allen; Jason M. Scheffler (EDIS)
This publication aims to provide a list of common hazards to consider when manufacturing poultry feeds. Written by Jessica Brown, Ashley Cavallo, Lindsay Zombek, Carli Brown, Arianna Minnie, Mindi Dennis, Gabrielle Allen, and Jason M. Scheffler, and published by the UF/IFAS Department of Animal Sciences, October 2021.